Interferometric scattering microscopy and its combination with single-molecule fluorescence imaging. - Ortega Arroyo, J; Cole, D; Kukura, P (Nature, 2016)
Interferometric scattering microscopy (iSCAT) is a light scattering-based imaging modality that offers a unique combination of imaging speed and precision for tracking nanoscopic labels and enables label-free optical sensing down to the single-molecule level. In contrast to fluorescence, iSCAT does not suffer from limitations associated with dye photochemistry and photophysics, or the requirement for fluorescent labeling. Here we present a protocol for constructing an iSCAT microscope from commercially available optical components and demonstrate its compatibility with simultaneously operating single-molecule, objective-type, total internal reflection fluorescence microscopy. Given an intermediate level of experience with optics and microscopy, for instance graduate-level familiarity with laser beam steering and optical components, this protocol can be completed in a time frame of 2 weeks.